Deep brain stimulation for chronic pain: mechanisms, clinical applications, limitations, and future directions - Al-Husinat, Lou’I; Al-Bataineh, Majdala; Hayajneh, Rama; Haneyah, Dania O.; Alrawabdeh, Qabas; Bani Melhem, Rasha; Al Sharei, Aiman; Ismail, Mohammed I.; Azzam, Saif; Al Sharie, Sarah; Varrassi, Giustino (Frontiers in Medicine, 2025)
Chronic pain is a complex, multifactorial condition affecting millions worldwide, which is often resistant to conventional treatments. Deep brain stimulation (DBS), a reversible and adjustable neurosurgical intervention, has emerged as a promising therapeutic approach for the treatment of resistant chronic pain. This narrative review examines the evolving clinical role of DBS in pain management, highlighting its mechanisms, efficacy, limitations, and future directions. We discuss the neurophysiological underpinnings of chronic pain, emphasizing structural and functional changes in brain regions such as the medial prefrontal cortex, limbic system, and somatosensory pathways. DBS targets, including the periaqueductal/periventricular gray (PAG/PVG), the sensory thalamus, the anterior cingulate cortex (ACC), and the ventral striatum, are investigated in terms of pain modulation and affective processing. Clinical studies demonstrate significant variability in response rates, largely influenced by patient selection, lead placement, and pain etiology. While DBS shows the greatest success in nociceptive and neuropathic pain syndromes such as cluster headaches, phantom limb pain, and failed back surgery syndrome, its efficacy in deafferentation pain remains limited. Recent innovations, including dual-target stimulation, advanced imaging for surgical planning, and combination therapies with spinal cord or vagal nerve stimulation, offer promising avenues for improving outcomes. Despite its off-label status for pain in many countries, accumulating data support DBS as a viable treatment in select cases of intractable pain. Continued research and standardized protocols are essential for optimizing patient selection, refining targeting strategies, and improving long-term outcomes.